PLASMA MEMBRANE INTEGRITY OF BULL SPERMATOZOA AT DIFFERENT STAGES OF PROCESSING OF SEMEN - SHUKLA, M K; SAHA, SUJIT; MISHRA, G K; SAXENA, S K (The Indian Journal of Animal Reproduction, 2011)
Present investigation was carried out on 51 semen ejaculates (26 from Holstein Friesian and 25 from crossbred bulls) collected from ten bulls maintained at Animal Breeding Centre, Salon, Rae Bareli (UP). Plasma membrane integrity of sperms at various stages of cryo-preservation was studied with the help of Hypo Osmotic Swelling Test (HOST). The results obtained revealed that the process of cryopreservation adversely affected the plasma membrane integrity. Percentage of HOST reacted sperms was reduced by more than 20 percent after freezing. There was a highly significant positive correlation (r=0.43) between number of HOST reacted sperms after dilution and after freezing. Too early (<15 minutes) or any delay in processing time(> 30 minutes) was found to have adverse effect on sperm plasma membrane integrity. A non significant but negative correlation was observed between the processing time and % of HOST reacted sperms after equilibration (r = -0.19) and freezing (r = -0.22).